Determination of the effective dose of oliceridine combined with propofol using the modified Dixon’s up-and-down method in painless gastroscopy - Cao, Jinfeng; Gu, Xiaoyu; Zhang, Xinyang; Cheng, Yao; Jiang, Liuqin (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate the median effective dose (ED50) and 95% effective dose (ED95) of oliceridine combined with propofol for painless gastroscopy in adults.MethodsPatients underwent painless gastroscopy were divided to male and female cohorts. A modified Dixon’s up-and-down sequential method was employed, with an initial oliceridine dose of 20 μg·kg−1 for both cohorts. Subsequent dosing adjustments were determined by the procedural success or failure of the preceding patient. The oliceridine dose was increased or decreased by a ratio of 1:1.2 for positive responses or negative responses. We recorded the time of successful induction, examination time, vital signs (HR, SpO2 and MAP) at predefined phases (including baseline T0, post-induction time T1, completion time T2, and departure time T3), induction dose and total dose of propofol, dose of oliceridine, intraoperative adverse events (including hypoxemia, respiratory depression, hypotension, and bradycardia), postoperative adverse events (including nausea, vomiting, and dizziness), and vasoactive agent administration during the procedure. Probit analysis was subsequently performed to determine the ED50, ED95 and corresponding 95% confidence intervals (CIs) of oliceridine in painless gastroscopy combined with propofol.ResultsThe ED50 and ED95 of oliceridine combined with propofol were determined as 12.63 μg·kg−1 (95% CI: 11.43–13.79) and 14.46 μg·kg−1 (95% CI: 13.41–20.33) in males, and 10.38 μg·kg−1 (95% CI: 9.02–11.96) and 13.19 μg·kg−1 (95% CI: 11.62–28.23) in females. Male negative subgroup required higher oliceridine doses (P < 0.05), while female negative subgroup had lower total propofol dose yet higher oliceridine doses (P < 0.05). Females in the negative subgroup used more propofol (P < 0.05), and both sexes’ negative subgroups consumed more oliceridine (P < 0.05). In males, SpO2 rose at T1 and T2 (P < 0.01), and MAP dropped at T2 and T3 (P < 0.05). In females, HR decreased at T2 (P < 0.05), SpO2 increased at T1 (P < 0.05), and MAP fell at T2 and T3 (P < 0.05). Adverse events included postoperative dizziness (12.50%), nausea (4.17%), and fatigue (4.17%) in females, and vomiting (5.56%) in males.ConclusionThe use of oliceridine (13.19–14.46 μg·kg−1) and propofol was associated with safety, efficacy, and lower complication rates during painless gastroscopy.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=249883, identifier ChiCTR2400093609